Coexistence or a related condition: an infant with retinoblastoma and Gaucher disease - Burcu Berberoğlu-Ateş; Ali Varan; Hülya Demir; Canan Akyüz; Aysel Yüce (The Turkish Journal of Pediatrics)
Gaucher disease (GD) is the most prevalant lysosomal lipid storage disease that results from loss of function of acid β-glucosidase due to mutations in the glucocerebrosidase gene. Common features of all types of GD include hepatosplenomegaly, cytopenia, and various patterns of bone and lung involvement. Retinoblastoma is a malignant tumor of the developing retina that occurs in children, typically before the age of five. Retinoblastoma develops from cells that have cancer-predisposing variants in both copies of RB1. The association between GD and retinoblastoma has not been reported until now. Here we report the case that was diagnosed with, retinoblastoma at the age of 2 months and then GD at the age of 11 months. Although there are controversies concerning the association between GD and cancer; malignancies should be kept in mind during GD patients follow up.